The effect of water running on the functional rehabilitation of medial tibial stress syndrome - T'Jonck, L.; Colman, V.; Persyn, U.; De Weerdt, W.; Lysens, R. (Biomechanics and Medicine in Swimming VIII, 1999)
The purpose of this study was to document the effect of a five-week running in water training programme on the rehabilitation of medial tibial stress syndrome. An endurance test using a bicycle ergometer, strength-tests on a Cybex dynamometer, functional tests and a subjective pain score on an absolute visual analogue scale were performed. The total increase in V02 max (llmin) for the water trained subjects (N=ll) was 7.5%, whereas the controls (N=lO) showed a decrease of 3.9%. The strength test results for the plantar and dorsal flexors were inconclusive. The pain scores improved in the trained group. In the pre-test water runners experienced moderate to severe pain (3 .1 to 10 cm on the visual analogue) in 9 out of 17 legs with medial tibial stress syndrome, whereas only 4 were so classified post test. In the control group 7 out of 18 extremities gave moderate or severe pain both before and after. In the water group a trend of increased activity level post training was noted. It is concluded that water therapy is an excellent alternative training programme for medial tibial stress syndrome by maintaining and even improving the condition. However only a trend of decreased discomfort was observed in the water trained subjects.